A retrospective on fundamental cause theory: State of the literature, and goals for the future - Clouston, Sean A P; Link, Bruce G (Annual review of sociology, 2021)
Fundamental Cause Theory (FCT) was originally proposed to explain how socioeconomic inequalities in health emerged and persisted over time. The concept was that higher socioeconomic status helped some people to avoid risks and adopt protective strategies using flexible resources - knowledge, money, power, prestige and beneficial social connections. As a sociological theory, FCT addressed this issue by calling on social stratification, stigma, and racism as they affected medical treatments and health outcomes. The last comprehensive review was completed a decade ago. Since then, FCT has been tested, and new applications have extended central features. The current review consolidates key in the literature in order to guide future research in the field. Notable themes emerged around types of resources and their usage, approaches used to test the theory, and novel extensions. We conclude that after 25 years of use, there remain crucial questions to be addressed.